2022
DOI: 10.14715/cmb/2022.68.2.28
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different solutions in tracheal suctioning on the incidence of pneumonia in patients on the ventilator

Abstract: Ventilator-associated pneumonia (VAP) is a common nosocomial infection in patients admitted to intensive care units (ICU), leading to prolonged stay in the ICU, increased hospital costs, and mortality. This study aimed to compare the effect of using normal saline with eucalyptus in endotracheal suctioning on the rate of ventilator-dependent pneumonia. For this purpose, a randomized clinical trial study was performed on 120 patients under a ventilator in the hospital ICU. Patients were randomly divided into con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Adhering to our complaint procedure, an investigation was conducted by the Editorial Office and Editorial Board, which confirmed that a significant number of randomized control trials reviewed were not eligible to be included in the analysis of this systematic review and meta-analysis. Specifically, the inclusion of Chai et al [2], Chow et al [3], Philippart et al [4] and Qiao et al [5] was considered to have limited relevance to the main topic of this systematic review and meta-analysis, and consequently, was judged to sufficiently compromise the overall findings to a degree that the findings could not be relied upon. Moreover, as a result of this methodological flaw, erroneous analysis and interpretation of the findings was performed.…”
mentioning
confidence: 99%
“…Adhering to our complaint procedure, an investigation was conducted by the Editorial Office and Editorial Board, which confirmed that a significant number of randomized control trials reviewed were not eligible to be included in the analysis of this systematic review and meta-analysis. Specifically, the inclusion of Chai et al [2], Chow et al [3], Philippart et al [4] and Qiao et al [5] was considered to have limited relevance to the main topic of this systematic review and meta-analysis, and consequently, was judged to sufficiently compromise the overall findings to a degree that the findings could not be relied upon. Moreover, as a result of this methodological flaw, erroneous analysis and interpretation of the findings was performed.…”
mentioning
confidence: 99%